Research futures: Projecting agricultural R&D potentials for Latin America and the Caribbean - Pardey, Philip G.; Wood, Stanley; Hertford, Reed (Inter-American Development Bank, 2010)
This volume offers substantive clarification of the proper roles for public agricultural research and development (R&D) throughout Latin America and the Caribbean (LAC) and introduces an analytical framework for assessing cross-country collective action in funding and carrying out research. To inform research policy decisions, the book provides a wealth of newly digested information about trends in agricultural production, productivity, consumption, and trade for the region, placing those trends in a comparative international context. It also provides new information about the spatial patterns of agricultural production and productivity in LAC— especially critical information for making informed research priority decisions given the inherent agroecological specificity of many agricultural technologies.